Effect of heat treatment on activity of staphylococcal enterotoxins of type A, B, and C in milk - Necidová, L; Bursová, Š; Haruštiaková, D; Bogdanovičová, Kateřina; Lačanin, I (Journal of dairy science, 2019)
Intoxication by staphylococcal enterotoxins (SE) is among the most common causes of food-poisoning outbreaks resulting from the consumption of raw milk or products made thereof. The aim of our study was to analyze the thermal stability of SE and evaluate the inactivation of SE types A, B, and C (SEA, SEB, SEC) by autoclaving at 100°C, 110°C, and 121°C. Milk samples were inoculated with 38 Staphylococcus aureus strains that possessed the ability to produce SEA, SEB, or SEC and incubated at 37°C for 24 h. This incubation was followed by heat treatment at 100°C, 110°C, or 121°C for 3 min. Samples were analyzed by Staph. aureus plate count method on Baird-Parker agar and specifically for the presence of SE. An enzyme-linked immunofluorescent assay (ELFA) on a MiniVIDAS analyzer (bioMérieux, Marcy l'Étoile, France) was used to detect SE, which were determined semi-quantitatively based on test values. The obtained results were analyzed by means of nonparametric statistical methods. All samples (100%; 38/38) were SE-positive before heat treatment, and the positivity rates decreased after heat treatment at 100°C, 110°C, and 121°C to 36.8% (14/38), 34.2% (13/38), and 31.6% (12/38), respectively. The rates of positive samples differed between SEA, SEB, and SEC producers: SEA was detected in the highest amounts both before and after heat treatment. The amount of SE (expressed as test values) decreased significantly after heat treatment. Comparing amounts of SE in positive and negative samples before and after heat treatment, we can conclude that the success of SE inactivation depends on the amount present before heat treatment. The highest amount of SE and the highest rate of SE-positive samples after all heat treatments were found in samples with strains producing SEA. For SEB and SEC, lower amounts of enterotoxin were present and were inactivated at 100°C. Although temperatures of 100°C, 110°C, and 121°C may inactivate SE in milk, the key measures in prevention of staphylococcal enterotoxicosis are avoiding initial contamination of milk by Staph. aureus, promoting consumption of heat-treated milk, and preventing disruption of the cold chain during milk production and processing.
Keywords: Staphylococcal Infections; Staphylococcus aureus; Refrigeration; Drug Stability; vysoká teplota; Hot Temperature; stafylokokové infekce; zvířata; chlazení; Food Microbiology; Mastitis, Bovine; Cattle; Milk; skot; stabilita léku; mastitida skotu; Animals; mléko; Enterotoxins; enterotoxiny; potravinářská mikrobiologie